HADITHS SCEPTICISM AUTHENTICITY (Critique to Orientalist Gautier H.A. Juynbool in Common Link Theory) - Dozan, Wely; Fahrurazi, Fahrurazi (Hunafa: Jurnal Studia Islamika, 2020)
This paper tries to discuss the thought of hadith in the eyes of the Orientalist one of them is Gautier H.A. Juynbool in theory is known as the common link which is the oldest narrator in the level of sanad after the best friend or tabiin who is responsible for spreading the hadith extensively either formally or informally to some students, then these students spread the hadith to several students as well . In other words, the common link is found in the Sanad bundle where the hadith was first spread. There are several terms in the analysis, including: First, Single Strand (Single Track). Second, Partial Common Link. Third, Invertedpartial Common Link. Fourth, Fulan, Fifth, Diving Strand. Sixth, Spider (spider). The approach used is the literature study approach is a search for related data through books, journals, articles and so on. The conclusion is that, the theory (common link) if applied in the hadith still the hadith does not come from the Prophet but the hadith comes from the tabi'in which is transmitted to the next generation.